IC 8591 Historical Injury Experience In The Nonmetallic Mineral Industries (Except Stone And Coal) (In Two Parts) 1. 1966-67 - Donald E. Redmon (The National Institute for Occupational Safety and Health (NIOSH), 1973)
This Bureau of Mines report reviews injury experience in the nonmetallic mineral industries (except stone and coal) for 1966-67. For each of the years, 23 tables summarize disabling work injuries by department, source of injury, extent of disability, part of body injured, and nature of injury. Correlative information on employment, worktime, and operating activity is also presented.